The combined use of photobiomodulation therapy and platelet-rich fibrin for the management of two MRONJ stage II cases: An alternative approach - Valamvanos, Konstantinos; Valamvanos, Theodoros-Filippos; Toumazou, Spyridon; Gartzouni, Eleni (Frontiers in Dental Medicine, 2022)
Medication-related osteonecrosis of the jaws (MRONJ) is a relatively rare but serious adverse drug reaction in patients under bone-targeting or antiangiogenic medication for malignant or osteometabolic diseases. The pathogenesis of MRONJ is multifactorial with the inhibition of osteoclasts and angiogenesis considered to play a key role in an individually susceptible environment, thus its prevalence is highly differentiated according to each study. Even though MRONJ has been reported since 2003 and the literature is expanding rapidly about possible risk factors, prevention and treatment options, the successful management with no recurrence is still under controversy. The conservative non-surgical (optimal oral hygiene, systemic antibiotic therapy) and surgical procedures (debridement, sequestrectomy or bone resection) are considered the treatment of choice especially at the early stages. Adjuvant therapies have been proposed to further stimulate bone and tissue healing such as teriparatide, bone morphogenic proteins, platelet concentrates, hyperbaric oxygen, ozone therapy, photodynamic therapy and lasers with promising results. The need to develop minimally invasive treatment protocols using novel technologies in particular for those patients with severe medical histories has been highlighted in the literature. The clinical protocol that has been developed in our dental department, which is effectively contributing to MRONJ management and combines Photobiomodulation therapy (PBMT) with platelet-rich fibrin (A-PRF), will be presented in this article.